A study of the role of metallothionein in the inherited copper toxicosis of dogs. - Hunt, D M (1986)
The role of metallothionein (MT) was assessed in the copper-loading disease prevalent in Bedlington terriers. Fractionation of tissue supernatants over Sephadex G-75 showed that most of the additional cytosolic copper present in liver tissue of these dogs was bound to MT, and that substantially more MT-bound copper could be solubilized by detergent plus mercaptoethanol. Zinc contents were only slightly raised, although most of the extra zinc was associated with a 4000-Mr ligand. Ion-exchange chromatography revealed two isoproteins, MT1 and MT2, in all the dog liver samples examined. In Bedlington terrier liver, copper associated with both isoproteins was increased, although the increase for MT2 was greater than for MT1. The content of MT protein was also raised, although cell-free translations and RNA blots of total liver RNA showed that this increase was not associated with a rise in MT mRNA. The significance of these results to the mechanism of copper accumulation in the Bedlington terrier disorder is discussed.